Improvements of insulin resistance in ovariectomized rats by a novel phytoestrogen from Curcuma comosa Roxb - Prasannarong,M. (BioMed Central, 2015)
Background: Curcuma comosa Roxb. (C. comosa) is an indigenous medicinal herb that has been used in Thailand as a dietary supplement to relieve postmenopausal symptoms. Recently, a novel phytoestrogen, (3R)-1,7-diphenyl-(4E,6E)-4,6-heptadien-3-ol or compound 049, has been isolated and no study thus far has investigated the role of C. comosa in preventing metabolic alterations occurring in estrogen-deprived state. The present study investigated the long-term effects (12 weeks) of C. comosa hexane extract and compound 049 on insulin resistance in prolonged estrogen-deprived rats.Methods: Female Sprague-Dawley rats were ovariectomized (OVX) and treated with C. comosa hexane extract (125 mg, 250 mg, or 500 mg/kg body weight (BW)) and compound 049 (50 mg/kg BW) intraperitoneally three times per week for 12 weeks. Body weight, food intake, visceral fat weight, uterine weight, serum lipid profile, glucose tolerance, insulin action on skeletal muscle glucose transport activity, and GLUT-4 protein expression were determined.Results: Prolonged ovariectomy resulted in dyslipidemia, impaired glucose tolerance and insulin-stimulated skeletal muscle glucose transport, as compared to SHAM. Treatment with C. comosa hexane extract and compound 049, three times per week for 12 weeks, markedly reduced serum total cholesterol and low-density lipoprotein levels, improved insulin sensitivity and partially restored uterine weights in ovariectomized rats. In addition, compound 049 or high doses of C. comosa hexane extract enhanced insulin-mediated glucose uptake in skeletal muscle and increased muscle GLUT-4 protein levels.Conclusions: Treatment with C. comosa and its diarylheptanoid derivative improved glucose and lipid metabolism in estrogen-deprived rats, supporting the traditional use of this natural phytoestrogen as a strategy for relieving insulin resistance and its related metabolic defects in postmenopausal women. © 2012 Prasannarong et al; licensee BioMed Central Ltd.